Psychosocial assistance to children - Ajduković, Dean (Array, 1999)
In the chapter pivotal concepts are defined and discussed from the extensive research and practical experience in dealing with the consequences of organized violence that affected large numbers of children and families who live under difficult circumstances and distress. Psychological sequela specific to the populations exposed to traumatic experiences and extremely difficult circumstances of life served as a framework to analyze the community response to the needs. The focus is on the difficulties in the adjustment of children to new circumstances that can be manifested in different forms of problem behaviors and relationship difficulties. Distressed adults usually pay little attention to the indicators of the psychological problems of these children. Among them we find distorted perceptions of the current situation, acute and severe changes in their emotions and behavior, such as depression, an increased sense of insecurity, lack of self confidence, inability to concentrate, extreme forgetfulness, anhedonia, suicidal thoughts, sleep disorders, appetite changes, enuresis, lack of trust, idealization of lost loved ones, homes and community. In addition, they develop a sense of hopelessness and helplessness with a deep sense of demoralization, seeing their futures as bleak. Somatic complaints and psychosomatic symptoms (ill-defined bodily aches and pains, i.e. stomachaches, headaches, difficulty in breathing, skin rashes etc.) can be an indicator of the child's emotional turmoil. Key elements of psychosocial assistance programs are related to the needs of affected children.